Effects of a 10 week training programme on physical parameters in Malaysian football referees / Subramaniam Nathan - Subramaniam, Nathan (2016)
The objectives of this study were to investigate the effectiveness and acceptability of a 10 week training programme to improve the physical parameters namely repeated short sprints, repeated high intensity intermittent runs and aerobic power in Malaysian football referees. It also investigated whether there was a significant difference in the two training methods used. Sixty national football referees (purposive sampling) participated in this study. The participants were randomly assigned (fishbowl method) into three different groups namely Experimental Group 1, Experimental Group 2 and Control Group. Each group comprised of 20 participants. Experimental Group 1 strictly followed a 10 week training programme supervised by qualified trainers. They trained for three days in a week. Experimental Group 2 also reported for training three days a week at a different venue and trained using their own training programme. The design of this study focused upon the individual performances in physical parameters in the pre-test, providing training for 10 weeks and determining if the referees improved in the three variables using post-test results. A mixed between-within subject analysis known as split-plot ANOVA (SPANOVA) was used to test the objectives. The comparison of pre-test and post-tests results indicated that there was a statistical significant difference in performance of Experimental Group 1 in repeated short sprints t (19) =20.2, p<0.05. Repeated high intensity intermittent runs t (19) = 22.4, p<0.05. Aerobic power t (19) = 19.4, p<0.05. There was also statistical significant difference in performance of Experimental Group 2 in repeated short sprints t (19) = 3.3, p<0.05. Repeated high intensity intermittent runs t (19) = 8.6, p<0.05. Aerobic power t (19) = 5.6, p<0.05. The results of Control Group indicated that there was a statistical significant difference in performance in repeated high intensity intermittent runs t (19) = 2.18, p<0.05. As for repeated short sprints and aerobic power there was no statistical significant difference. iv Repeated short sprints t (19) = 0.4, p>0.05. Aerobic power t (19) = 0.7, p>0.05. Further, the results indicated that there was a significance difference in the performance of the three groups in repeated short sprints after 10 weeks of training [F (2, 57) =154.75, p<0.05]. As for repeated high intensity intermittent runs, it was found that there was a significant difference in the performance of the three groups after 10 weeks. [F (2, 57) =75.86, p<.05]. Finally, as for aerobic power, the results showed that there was a significant difference in the performance of the three groups after 10 weeks.[F (2, 57) =141.18, p<.05]. The results of multiple comparisons among groups indicated that the performance of all the three groups differed from one another with Experimental Group 1 showing the best performance and the Control Group the poorest. The results provide meaningful support for the conclusion that a planned training programme is likely to be effective and acceptable to improve performance in repeated short sprints, repeated high intensity intermittent runs and aerobic power of football referees. The training programme therefore, can be adopted as a formal training programme for football referees.